Factors associated with sexual engagement among schooling adolescents in Sarawak, East Malaysia - Cheah, Whye Lian; Halimah, Awang; Chang, Ching Thon; Low, Wah Yun; Tong, Wen Ting; Dev Nath, Kushal; Hamizah, Mohd Hassan (Nova Science Publishers, Inc., 2020)
This study examined the factors of sexual behaviours among schooling adolescents in Sarawak. Respondents for the study were adolescents aged 13 to 19 years from 16 secondary schools in Sarawak using self-administered questionnaire. Information on socio-demographic characteristics, knowledge on and attitudes towards sexual and reproductive health, involvement in risky lifestyle and sexual activities, family relationships, school attachment and religious beliefs were obtained. Chi-square tests and logistic regression analysis were performed to examine factors associated with sexual intercourse. A total of 1,462 students participated in the study, with 60.1% female respondents, mean age 15.6 ± 1.72 years old. The prevalence of sex engagement was 3.6%, majority aged 16-17 years (58.5%). Mean age at first sexual intercourse was 16.8 ± 1.27 years, with a minimum age of 14 years. Age of respondents, knowledge on SRH, risky behaviours, peers’ risky behaviours, negative self-evaluation, cognitive inefficiency, perceived lack of motivation, religious belief and family support were significantly associated with sexual engagement. Logistic regression showed that age, respondents’ risky behaviour and peers’ involvement in sexual intercourse were significant risk factors of sexual engagement while a strong religious belief was a significant protective factor. Although the prevalence of sexual engagement was quite low compared to many other countries, there is a need to strengthen comprehensive sexual health education both at the school and community levels. It is important for adolescents to make informed decisions on their risky sexual behaviours as there are serious consequences of such behaviours on their current and future life.